Unconventional Monetary Policy and Long-Term Interest Rates - Wu, Tao. (Washington, D.C. : International Monetary Fund, 2014)
This paper examines the transmission mechanism through which unconventional monetary policy affects long-term interest rates. I construct a real-time measure summarizing market projections of the magnitude and duration of the Federal Reserve's Large Scale Asset Purchases (LSAP) program, and analyze the determination of term premiums and expectations of future short-term interest rates in a sample spanning more than two decades. Empirical findings suggest that the LSAP has effectively lowered the long-term Treasury bond yields, through both "signaling" and "portfolio balance" channels. On the other hand, the Fed's "forward guidance" also leads to gradual extension of market projections for the duration of the LSAP program, thereby enhancing the LSAP's effect to keep term premiums low. Estimation results also reveal a diminished effectiveness of the LSAP during QE III. Finally, model simulations underscore the importance of policy transparency in minimizing unnecessary market turbulence and ensuring a timely and smooth exit of the unconventional monetary policy stimulus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet